REPRESENTASI PEREMPUAN BANGKA BELITUNG DALAM NOVEL-NOVEL PARA PENULIS PEREMPUAN BANGKA BELITUNG: KAJIAN FEMINISME - Andri Fernanda; Ranto Ranto (BASIS (Bahasa dan Sastra Inggris), 2021)
The goal of this study was to break down gender issues and stereotypes towards women constructed in Bangka Belitung society from the perspective of female authors. In analyzing the data, researchers carried out a qualitative descriptive method with feminist theory. The researchers also conducted critical discourse analysis on writings that have been published by Bangka Belitung’s female authors. The results showed that there were still gender inequality and inferiority of women in society. The identity crisis faced by women when they are not married since marriage is seen as an ideal as well as a complement to their life as real women in society. On the other hand, the picture of how women had no rights over themselves was demonstrated in a situation when matchmaking and marriage were performed one-sidedly and suddenly, women did not have enough power to question these, even refused them. Besides, how strong a patriarchal system and culture was shaped by women, their closest people and the community was proven in the novels of the Bangka Belitung’s female authors.